Respuesta :

To solve the formula for v1, we must get this variable alone on one side of the equation. To do this, we use the reverse order of operations to move the other variables to the other side of the equation.

First, we begin by multiplying both sides of the equation by t, so that we can get rid of the denominator on the right side.

a = (v1 - v0)/t

a(t) = v1 - v0

Next, we must add v0 to both sides of the equation. This will get the variable v1 completely alone on the right side of the equation, giving us our answer.

(at) + v0 = v1

We should rearrange the equation so that v1 is the left side of the equation.

v1 = at + v0 (your answer)

Hope this helps!

gmany

[tex] \dfrac{v_1-v_0}{t}=a\ \ \ |\cdot t\neq0\\\\v_1-v_0=at\ \ \ |+v_0\\\\v_1=at+v_0 [/tex]